Finite element analysis of disc brake squeal and its suppression approach - Saw, Chun Lin; W.M.M. Wan Harujan; A.R. Abu-Bakar; B.A. Ghani (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.